2018
DOI: 10.11604/pamj.2018.30.155.14886
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B virus infection among sexually active individuals in Nigeria: a cross-sectional study

Abstract: IntroductionHepatitis B virus (HBV) infection is a major health challenge in sub-Saharan African countries. Chronic HBV infection is a risk factor for severe disease progression. Perinatal and sexual transmissions of Hepatitis B virus are the main routes of infection in HBV endemic countries like Nigeria. However, there is paucity of data as regards the major contributory route of transmission to chronic HBV infection in this region. Also, in Nigeria, not everyone at high risk of the infection has been identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 25 publications
4
9
0
Order By: Relevance
“…However, a similar prevalence rate of 8.50% was reported quite recently in an epidemiological study in 2012 [46]. The results of this review are lower than the >8.80% reported in other parts of West Africa [47][48][49] and the prevalence for the African region at large [2]. For instance, a meta-analysis reported that the pooled prevalence of HBV in the Nigerian population is 13.6% [50].…”
Section: Discussionsupporting
confidence: 79%
“…However, a similar prevalence rate of 8.50% was reported quite recently in an epidemiological study in 2012 [46]. The results of this review are lower than the >8.80% reported in other parts of West Africa [47][48][49] and the prevalence for the African region at large [2]. For instance, a meta-analysis reported that the pooled prevalence of HBV in the Nigerian population is 13.6% [50].…”
Section: Discussionsupporting
confidence: 79%
“…The >50 age group were the second to the least of the subjects (9% females and 12% for females). This finding is in agreement with that of Yewande et al, [27]. The children (<20) and the aged (>50) have less exposure to risky behaviours than the middle aged (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40).…”
Section: Discussionsupporting
confidence: 90%
“…The sex distribution of the subjects in this study showed that there were more males 100(57.2%) males and 76(42.8%) females. This shows that HBV infection is more prevalent in males than females and the finding is in keeping with the findings of Yewande et al, [27] which reported males are 2.8 times more likely to get infected with HBV compared to their female counterparts [7]. This could be due to the fact that males are more prone to risk factors and behaviors sexual intercourse, injection drug use, barbing et ce tera which predispose them to HBV infection.…”
Section: Discussionsupporting
confidence: 89%
“…Both health care workers and those who inject drugs into their veins are at risk in this way [14,31].  Having sex with a person infected by HBV is an important risk factor (especially anal sex) [32].…”
Section: Descriptionmentioning
confidence: 99%